Study the impact of process parameters and electrode material on wire electric discharge machining performances. (2018) - Sen, Ruma; Choudhuri, Bikash; Barma, John Deb; Chakraborti, Prasun
Abstract: Wire electric discharge machining (WEDM) is an advance manufacturing process for machining hard materials. The machining efficiency and productivity of WEDM not only depends on machining parameters but also improved by proper selection of electrode material. In this investigation brass wire and silver coated brass wire are selected as electrode material to evaluate the influence of wire material on WEDM machining performances. From analysis of variance, it was reveals that pulse on time, servo voltage is one of the dominant parameters. Machining with silver coated brass wire found to be best alternative of brass wire on the Maraging steel 300.